Coronavirus Disease 2019 (COVID-19) pandemic, lessons to be learned! - Islam, Md Saiful; Sobur, Md Abdus; Akter, Mily; Nazir, KHM Nazmul Hussain; Toniolo, Antonio; Rahman, Md Tanvir (Journal of Advanced Veterinary and Animal Research, 2020)
Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been reported as a worldwide emergency. Due to the extensiveness of spread and death, it has been declared as a pandemic. This review focused on the current pandemic situation and understanding the prevention and control strategies of COVID-19. Data presented here was by April 3, 2020. A total of 1,016,399 cases of COVID-19 with 53,238 deaths was reported from 204 countries and territories including two international conveyances over the world. After China, most of the new cases were from Europe, particularly Italy acting as the source of importation to many of the other countries around the world. China has obtained success by ascribing control strategies against COVID-19. The implementation of China’s strategy, as well as the development of a vaccine, may control the pandemic of COVID-19. Further robust studies are required for a clear understanding of transmission parameters, prevention, and control strategies of SARS-CoV-2. This review paper describes the nature of COVID-19 and the possible ways for the effective controlling of the COVID-19 or similar viral diseases that may come in the future. Adv. Vet. Anim. Res., 7(2): 260-280, June 2020